2014
DOI: 10.1089/cap.2013.0116
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Antipsychotics in Prepubertal Children: A Retrospective Chart Review

Abstract: We found a significant increase in both absolute weight gain and BMI percentile following atypical antipsychotic treatment. In contrast, typical antipsychotic treatment did not affect weight gain significantly, and the same was true for the control group. In addition, the rates of elevated values of biochemical parameters (AST, ALT, total cholesterol, triglycerides, and fasting blood glucose levels) were very low at the beginning of the study, and were not significantly altered by the various treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…We identified 135 studies (57 new studies after the 2012 report 14 ) meeting our review criteria; of these, 126 (93%) reported on harms (Figure 1). 24 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 135 studies (57 new studies after the 2012 report 14 ) meeting our review criteria; of these, 126 (93%) reported on harms (Figure 1). 24 …”
Section: Resultsmentioning
confidence: 99%
“…c For weight and BMI, the effects were considered small when gains were approximately <1.5 kg and <1 kg/m 2 , respectively. 39,43,53,54,57,58,62,64,75,77,86,90,94,97,98,113,124,133,138,139,148 No 49,52,62,113,114,138 Not estimable 98 No significant difference Abbreviations: BMI, body mass index; CI, confidence interval; CrI, credible interval; EPS, extrapyramidal symptoms; FGA, first-generation antipsychotic; G1, group 1; G2, group 2; MD, mean difference; RR, risk ratio; SGA, second-generation antipsychotic.…”
Section: Fgas Versus Sgasmentioning
confidence: 99%
“…Compared to a control sample of untreated children, patients receiving SGAs presented significant overweight and obesity (OR = 3.1 and 3.6, respectively), and significant SGA-dependent increase in weight-z (+0.77 vs. -0.1) and BMI-z (+0.8 vs. +0.05) measures. Another study, with a 4-month follow-up, showed a greater weight increase with Risperidone, as compared to FGAs (+3.7 kg vs. + 0.9 Kg), and +13 kg and +4 BMI-z, with respect to untreated subjects, irrespective of drug exposure time (OS) [ 32 ]. A relevant study of 4280 adults and 179 adolescents, followed for up to 6 months, investigated the effect of age on Olanzapine-dependent weight gain [ 33 ].…”
Section: Introductionmentioning
confidence: 99%